BoLA-DRB3 exon2 polymorphisms among tuberculous cattle: Nucleotide and functional variability and their association with bovine tuberculosis pathology. (June 2020) - Eirin, M.; Carignano, H.; Shimizu, E.; Pando, M.A.; Zumárraga, M.; Magnano, G.; Macías, A.; Garbaccio, S.; Huertas, P.; Morsella, C.; Ferrara Muñiz, X.; Cataldi, A.; et al.
Abstract: Bovine tuberculosis (bTB) is caused by Mycobacterium bovis and disseminated worldwide. In Argentina, the highest prevalence occurs in dairy areas. BoLA DRB3.2 is related to the adaptive immunity in mycobacterial infections. Genetic polymorphisms of this marker have been associated with resistance or susceptibility to bovine diseases. We evaluated the association between BoLA DRB3.2 polymorphisms and bTB pathology scores in dairy and beef cattle breeds of Argentina. Most bovines exhibited visible lesions compatible with tuberculosis and, furthermore, 150 (85.7%) were also positive by bacteriology. A pathology index showed a variable degree of disease, from 3 to 76 (median pathology score = 9 (IQR: 7–15)). Thirty-five BoLA DRB3.2 alleles were identified with an associated frequency from 16% to 0.3%, distributed 73% ( n = 128) in heterozygosis and 27% ( n = 47) in homozygosis, with 12 BoLA DRB3.2 alleles (*0101, *1101, *1501, *0201, *2707 *1001, *1002, *1201, *14011, *0501 *0902 and *0701) representing the 74.7% of the population variability. A functional analysis grouped them in 4 out of 5 clusters (A-D), suggesting a functional overlapping. Among the 90 identified genotypes, *1101/*1101, *1101/*1501 and *0101/*0101 were the most frequent (10%, 8.9% and 8.9%, respectively). No association was detected between the pathology scores and a specific DRB3.2 allele ( p > .05 ). Animals infected with M. bovis spoligotype SB0153 showed a significantly higher pathology score than those affected by the spoligotype SB0145 ( p = .018 ). Furthermore, the Aberdeen Angus breed exhibited highest pathological scores ( p < .0001 ), which were associated with disseminated lesion, thus suggesting that the host component could be important to the disease progression. Highlights: BoLA DRB3.2 alleles were not associated to tuberculous pathological score. Cattle breed was associated to the tuberculous pathology score. Genomic variability of BoLA DBR3.2 alleles was higher than the functional. M. bovis strain, cattle category and geographic area influence disease progression.